Prostate‐specific antigen testing rates and referral patterns from general practice data in England. Issue 4 (14th March 2016) - Moss, S.; Melia, J.; Sutton, J.; Mathews, C.; Kirby, M.
Summary: Background: There is currently no national screening programme for prostate cancer in England, but eligible men can request a prostate‐specific antigen (PSA) test from their general practitioner (GP). There are no routinely available data to monitor the extent of PSA testing and referral. Aim: The aim of this study was to investigate the rate of PSA testing in general practice and subsequent patterns of referral. Design and setting: Data obtained from the Clinical Practice Research Datalink (CPRD) for men aged 45–84 years who had a PSA test during 2010–2011, registered in practices in England with linked Hospital Episode Statistics (HES) data. Method: Patient data were linked to previous tests and consultations. Rates of PSA testing and proportions of men retested and referred to secondary care were calculated. Results: Overall, 8.74 (95% CI 8.67–8.82) of men per 100 person‐years were tested at least once in 2010, and 9.45 (95% CI 9.37–9.53) in 2011. Rates increased with age and decreased with increasing level of deprivation. Of the 53, 069 men tested in 2010, 11, 289 (21.3%) had a previous PSA test within the past 12 months. Of men with raised PSA according to age specific guidelines, 22.4% (2113/9425) were referred to secondary care within 14 days, with 36% of the remainder retested within 6 months. Conclusions: Rates of PSA testing have increased compared with earlier studies; the data suggest that many GPs are retesting men with raised PSA rather than referring immediately. More routine data on PSA testing, including reasons for testing, and subsequent management and outcomes, are required.